Analysis of Student Engagement in Online Learning - Kishor Kumar Dash (AG Volumes, 2022)
For the purposes of this research, "online learning" refers to students who get their academic instruction through an online learning platform under the supervision of instructors. This paper’s major points are based on an examination of relevant research findings and on consideration of current issues: (1) examine and research the existing paradigm of student involvement, This research established the student engagement model based on the three aspects of student behaviour, knowledge, and emotion in light of the specifics of online learning activities. (2) Examine the level of behavioural involvement shown by students. Learning behaviour data is used to determine a student’s involvement level. Then, the same procedures were employed to determine student involvement levels. Students’ levels of involvement in learning should be measured using these behaviours as assessment markers. (3) A look at how engaged students are in their learning. Students’ cognitive involvement may be studied and analysed by studying relevant literature and analysing the content of the student’s educational programme. Students’ cognitive engagement levels are evaluated using the corresponding assessment index. (4) An evaluation of the extent to which pupils have experienced certain emotions It was determined that students’ emotional experiences could be quantified and analysed by using the self-evaluation approach, which was used during online learning.